An update on adverse health effects from exposure to PM2.5 - Sarawut Sangkham; Worradorn Phairuang; Samendra P. Sherchan; Nattapon Pansakun; Narongsuk Munkong; Kritsada Sarndhong; Md. Aminul Islam; Pornpun Sakunkoo (Environmental Advances)
The impact of fine particulate matter (PM2.5) on public health has become a global concern due to the mortality and morbidity it entails. Pathophysiological and epidemiological studies have demonstrated an association between PM2.5 and respiratory diseases, cardiovascular diseases, and neurological disorders. The underlying mechanisms through which PM2.5 adversely affects human health include the induction of oxidative stress, cytokine release, deoxyribonucleic acid (DNA) damage, altered gene expression, immune toxicity, inflammatory responses, and apoptosis. These outcomes drive the initiation and progression of various diseases. Notably, exposure to PM2.5 containing chemical compounds may translocate and induce unbalanced intracellular functions at the genetic and epigenetic levels, leading to mutations, carcinogenesis, and multiple diseases. This review aims to summarise and discuss recent updates on the mechanisms linking PM2.5 exposure to adverse health, highlighting the critical connection between PM2.5 and health outcomes, with the hope of raising awareness and promoting measures to reduce PM2.5 levels worldwide.